Menumbuhkan Sikap Kerukunan dalam Persepektif Iman Kristen Sebagai Upaya Deradikalisasi - Yonatan Alex Arifianto (UIN Sunan Gunung Djati Bandung, 2021)
Tolerance is very important for being together in a pluralistic society, there are incidents of intolerance that occur and there is a radical understanding of religion that does not uphold harmony. Creating horizontal conflicts that are very detrimental to society and the nation. From these problems, the writer uses literature research method with descriptive quantitative approach to answer the role of believers in fostering an attitude of harmony as part of deradicalization which aims to make Christians aware of the importance of maintaining harmony and peace in society as an important part of deradicalization. The conclusion from the discussion of this article is that believers must have an understanding that tolerance is part of the nation and state, so that an attitude will emerge to foster harmony as a spirit of peace. Then the role of Christians in being tolerant is made deradicalisation of the importance of living in multiculturalism. Because harmony becomes the unifying pillar in a plural society, in a beloved country. So that this research can provide insights and attitudes that promote harmony in society as part of deradicalization for the nation and state.